INNOVATIVE STRATEGIES FOR UKRAINIAN AGRIBUSINESS DEVELOPMENT IN THE POSTWAR PERIOD - Prokopyshyn , О.; Polehenka, М.; Zhydovska , Н. (Bulletin of Lviv National Environmental University. Series "AIC Economics", 2023)
The article describes the need and importance of the formation of a strategy for innovative development of Ukrainian agribusiness as the main prerequisite for increasing the level of competitiveness and the possibility of achieving a high level of development in the postwar period. It is determined that innovations generate positive structural shifts in the economy and society, contribute to the economy's efficiency, strengthen its ability to compete in the global environment with the economies of other countries of the world and ensure sustainable growth in the long term. The work analyzes key problems faced by agribusiness in the conditions of martial law and unstable geopolitical situations, in particular, reduced soil fertility, labor shortages, crop losses, and market instability. To solve these problems, the authors proposed to apply an innovative strategy for agribusiness development. The proposed strategy should include a thorough analysis of the internal resources of enterprises to introduce innovations, as well as the possibility of attracting external innovations by using external ideas considering the innovative infrastructure. The experience of successful companies in this domain testifies to the popularity of integrated, interactive, and network models of innovative development, which allow maximizing the possibility of developing innovative solutions and introducing them into production. Based on today's realities, the innovation strategy should include full vertical integration with the provision of the production of necessary material and technical resources and means of production, the development of green energy on the basis of more complete recycling, and the production of biofuels as an alternative type of energy, which will contribute to a reduction of the energy dependence, ensure the export of agricultural products and reconsideration of the set of cultivated crops with a focus on increasing productivity. The need to attract additional funding for the financial provision of innovative transformations in the form of new and unconventional financial instruments, i.e. innovative vouchers, crowdfunding systems, and blockchain technologies, has been substantiated.